PENGARUH KUALITAS LAYANAN MASKAPAI PENERBANGAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN - Gugyh Susandy; Estu Widarwati; Helna Hetriana (STIESA Press, 2023)
This study aims to determine the effect of aircraft service quality on customer satisfaction and loyalty. The most important step in identifying and delivering high-quality service is understanding exactly what customers expect. Service quality is one of the best models to measure customer expectations and perceptions. Company performance results in customer satisfaction with the product or service. Based on this model, the survey is described through an electronic questionnaire, all Stie Sutaatmadja students who use airlines are the target population. A total of 105 respondents were obtained who stated the use of airlines. The results of this study are that the service quality of AirAsia airlines has a significant effect on customer satisfaction and loyalty. Passenger satisfaction is important to customer sovereignty. Customers can be loyal without being very satisfied and be very satisfied, but not be loyal. In addition, the findings of this study will help airline managers to better serve their customers, track and improve service quality, and achieve the highest level of satisfaction for their passengers.